PENGARUH PEMBIAYAAN MUDHARABAH DAN MURABAHAH TERHADAP PERKEMBANGAN UMKM PADA ANGGOTA DI BMT TUMANG CABANG BOYOLALI - Muthmainah, Siti; Suryana, Alean Kistiani Hegy; Triatmaja, Nur Asih; Sulistyowati, Arrin; Nugroho Rachman, Arif (EKOBIS, 2025)
This study aims to determine the effect of Mudharabah and Murabahah financing on the development of UMKM members of the Tumang branch of Boyolali. This study uses primary data, namely data collection by distributing or providing several lists of statements that will be given to respondents and respondents will provide responses or answers to questions given by researcher. The sample used was 50 people taken from the customer population at the BMT Tumang Boyolali branch. Data analysis used is data instrument, classic assumption test and hypothesis test. And the result obtained partially are Mudharabah and Murabahah financing which is variable X1 with a significant value of 0,020 < 0,05 which means that H1 is accepted, thus it can be said that the mudharabah variable has a positive influence on the development of MSME. Murabahah financing is a variable X2 which has a significant value of 0,266 > 0,05 which means H2 is rejectec and it can be said that the murabahah variable has no significant influence on the development of MSME.